1964
DOI: 10.1161/01.cir.29.6.854
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Response to Exercise in Isolated Pulmonic Stenosis

Abstract: THE value of observations made during exercise in assessing the severity of isolated pulmonic stenosis has been recognized previously.1-4 Elowever, the small number of patients studied, the coincident occurrence of right-to-left shunting, and the paucity of comparable data in normal subjects have made for difficulties in interpretation. As a more precise assessment of the severity of pulmonic stenosis became necessary with the development of surgical technics for correction, exercise response was emphasized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1
1

Year Published

1966
1966
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
0
13
1
1
Order By: Relevance
“…10) Group V: Pulmonary Stenosis (27). The heemodynamic findings (Table II) reported from this laboratory (Johnson, 1962) and elsewhere (Joos et al, 1954;Lewis et al, 1964).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…10) Group V: Pulmonary Stenosis (27). The heemodynamic findings (Table II) reported from this laboratory (Johnson, 1962) and elsewhere (Joos et al, 1954;Lewis et al, 1964).…”
Section: Resultsmentioning
confidence: 74%
“…Here the effects of low cardiac output can therefore be seen in a purer form than in the other groups. Previous studies in such patients have yielded conflicting results: Sloman and Gandevia (1964) found a normal ventilatory response during upright exercise, while Lewis et al (1964) found an exaggerated ventilatory response during supine exercise. Our results indicate that about one-third of the patients with pulmonary stenosis hyperventilate during both supine and upright (Gazetopoulos et al, 1966) exercise.…”
mentioning
confidence: 91%
“…Consequently, exercise capacity is reduced due to an inability to increase stroke volume with the increase in heart rate being the sole contributor to an increase in cardiac output 5 6. Conversely, the natural evolution of mild PV stenosis is considered to be benign without progression of the valve gradient after adolescence and no deaths are observed during an 8-year follow-up period 3 7.…”
Section: Introductionmentioning
confidence: 99%
“…Some controversy exists with regard to indications for dilation in patients with moderate pulmonary stenosis and gradients in the range of 35 to 50 mmHg. Though these patients are likely to do very well for years, they demonstrate abnormally low maximal cardiac output, increased oxygen extraction, abnormal ventilatory responses, as well as marked increases in right ventricular pressures with exercise [17]. It is reasonable to consider valvuloplasty in such patients, though more long-term follow up will be required to clarify the best approach for this group.…”
Section: Critical Pulmonic Stenosis In the Newbornmentioning
confidence: 99%